The Effectiveness of the Family Hope Program as an Effort to Accelerate Poverty Alleviation in Balai Gadang Subdistrict, Koto Tangah District, Padang City - Melisa Nelson; Lince Magriasti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract The Family Hope Program (PKH) is a form of conditional social assistance from the government to promote the welfare of the poor through access to education, health, and social welfare. This study was conducted to determine the extent of the effectiveness of the Family Hope Program (PKH) as an effort to accelerate poverty reduction in Balai Gadang Village, as well as supporting and inhibiting factors in the implementation of PKH in Balai Gadang Village. The type of research used is qualitative research with descriptive methods. The selection of research informants used the Purposive Sampling technique, while the research data was obtained from interviews with research informants and Documentation Studies in Balai Gadang Village. This research data is strengthened by documentary evidence and data or documents available at the Balai Gadang Village office. The implementation of data analysis in this study uses data reduction, data presentation, and drawing conclusions. The results of the study can be concluded that there are still several supports and obstacles in the implementation of the Family Hope Program (PKH) such as the lack of validation of aid recipient data, low financial literacy of some KPM, and the number of companions who are still limited in reaching all target families. Keywords: effectiveness, poverty, family hope program